2010
DOI: 10.1007/s12541-010-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Study on the web deformation in ink transfer process for R2R printing application

Abstract: Web deformation occurring in the ink transfer process from the printing roller to the flexible web was investigated using a CFD technique for the application in roll-to-roll printed electronics. Analysis for the flow-structure interaction was conducted to assess the deflection and stress distributions of the web. To make the present analysis more relevant to the real printing system, both realistic geometric configuration and ink properties were set up using the information obtained from the typical roll-to-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…T . Equation (4) can be written as the dynamic equation (6) where M, L, H and D are matrices ((N × N), where N = m n), and M is non singular. Here D is the input matrix, and U is a dimensionless feedback control vector.…”
Section: State Equation Of Vibration Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…T . Equation (4) can be written as the dynamic equation (6) where M, L, H and D are matrices ((N × N), where N = m n), and M is non singular. Here D is the input matrix, and U is a dimensionless feedback control vector.…”
Section: State Equation Of Vibration Control Systemmentioning
confidence: 99%
“…If the vibration is not effectively controlled, it will seriously affect the quality of production [1][2][3][4][5]. Besides, after coating or printing, the density uniformity of the web is changed and the dynamic behavior of the web becomes more complex [6]. Thus, controlling the moving web with varying density effectively to reduce or avoid generating strong vibration is important.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study 20 reported that the time for the combined drying and curing processes could be successfully reduced by a factor of as large as 5. Therefore, higher web, handling speeds of up to 30 mpm (¼0.5 m/s) compared to the speeds chosen in previous studies, [17][18][19] was considered in this study. Obviously, a relatively higher speed shortens the convection time-scale, thus increasing the importance of the inertial effect relative to that of viscous action.…”
Section: Numerical Configuration and Parametersmentioning
confidence: 99%
“…They successfully illustrated the role of surface wettability and cavity size of their model. In more recent studies by Lee and Na 17,18 and Kim and Na, 19 the geometry of gravure printing, which is one of the most popular R2R printing methods, was considered for direct relevance to real applications. Kim and Na 19 showed that the characteristics of the transferred ink strongly depend on the magnitude of the viscosity under the assumption of Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation